FISHING BUSINESS ANALYSIS IN THE TELUK VILLAGE DISTIRCT OF KUALA KAMPAR IN PELALAWAN RIAU PROVINCE - Prisdont Dito; Hendrik '; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in October 2014 held at The Teluk Village District of Kuala Kampar Pelalawan Riau Province, the method used in this study is a survey method. The data collected is secondary data. Respondents in this study is fisherman in Teluk Village District of Kuala Kampar. Intake of informants is done by random sampling stratifid take informant randomly from each population, then the respondents is to support and strengthen the secondary data drawn from relevant agencies. This study aims to determine the total investment, revenue, business feasibility and the factors that affect fishing in the Teluk Villge District of Kuala Kampar Pelalawan Riau Province. Based on the results, the average fish catch every respondents is different that respondent 1 as much as 9132 kg every year, respondent 2 as much as 2,748 kg every year, respondent 3 as much as 2,376 kg every year and respondent 4 as much as 1,932 kg every year. The total investment in each of the respondents, total investment respondent 1 amounted to Rp.48.400.000, respondent 2 Rp. 22,000,000, respondent 3 Rp.19.800.000, respondent 4 Rp. 17,600,000. Net income respondent 1 Rp. 48.400.000 every year, respondent 2 Rp. 10.560.000 every year, respondent 3 Rp. 8.648.000 every year and respondent 4 Rp.6.796.000 every year. Revenue Analysis based on various criteria, RCR and PPC can be said to be worth fishing effort developed.Keywords: Income Analysis, RCR, PPC